VOAT: Voice Onset Analysis Tool - Arias Vergara, Tomás; Madill, Catherine; Nguyen, Duong; Holik, John; Döllinger, Michael (SoftwareX, 2024)
The onset of phonation can be used as a biomarker for quantitative voice assessment and identification of phonation type, e.g., breathy, modal, and creaky. The onset of phonation can be calculated considering different modalities: acoustic, electroglottography (EGG), airflow, and glottal area waveforms. Considering the potential of voice onset in clinical applications, we have been developing the Voice Onset Analysis Tool (VOAT), a computer-aided program written in Python for the semi-automatic detection of vowel phonation onset. VOAT can detect the vowel onset on recordings with multiple phonations. Furthermore, the user can manually select the segments from the recording where the onset is present or apply a voice activity detection for automatic segmentation. VOAT provides filtering options to facilitate the detection and allows the saving of results in an Excel file for further processing. Our software also allows batch processing to detect vowel onset on several files automatically.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Biomarker; Onset of phonation; Phonation onset time; Voice analysis